A new species of Mycodiplosis gall midge (Diptera: Cecidomyiidae) feeding on myrtle rust Austropuccinia psidii. Issue 2 (3rd July 2021) - Kolesik, Peter; Sutherland, Roanne; Gillard, Kristin; Gresham, Belinda; Withers, Toni M.
ABSTRACT: Larvae of an undescribed gall midge were found feeding on the rust fungus Austropuccinia psidii that was infecting leaves of trees Lophomyrtus bullata, Lophomyrtus obcordata and Syzygium jambos (all Myrtaceae) in New Zealand. The new species belongs to a cosmopolitan, rust- and mildew-feeding genus Mycodiplosis (Diptera: Cecidomyiidae). The description of Mycodiplosis constricta sp. nov. includes morphology of adults, pupa and larva, and the sequence of a segment of the Cytochrome Oxidase unit I mitochondrial gene. The new species differs from its congeners in an unusual aedeagus and a peculiar male hypoproct. The aedeagus is rounded apically and strongly constricted subapically, bearing subapical setulose sensoria. The hypoproctal lobes are long and narrow, dorsally they are covered with long apical setulae, ventrally they are bare, each lobe bearing a pair of setae of which one is placed apically, the other subapically. The currently known geographical distribution of the new species is confined to the North Island of New Zealand. While it is likely that larvae of the new species decrease numbers of viable uredinia of Austropuccinia psidii, the exact impact of the new species on the population dynamics of the fungal host as a biological control agent and/or a transmission vector remain to be determined. http://zoobank.org/urn:lsid:zoobank.org:pub:3D39F717-49E0-4B46-9033-BE5A244D6A39